Oligarchy In The Discourse On Poverty In The State Of Terengganu Darul Iman Malaysia - Syafhendry, Syafhendry; Setiawan, Rizky; Hakim, Arif Rahman; Salman, Ali; Lestari, Marianan Tri; Josinta, Josinta (Pasundan Community Service Development, 2025)
Oligarchy of power in government systems in the world has become a discourse and discussion among academics, researchers, practitioners and the public. Variants of oligarchy always mutate in each era of leadership, providing a strong influence on the running of government. Along with the increasing complexity of problems in administering government in the current era of global disruption, this has led to a shift in power orientation. The concept of a state of the people by the people and for the people, which is a reflection of democracy, is currently undergoing a shift. Investors collaborate with very dominant political elites in controlling the government. Groups that have political and economic power unite in circles of power or better known as oligarchy. The aim of this community service is to describe explicitly and comprehensively the concept of Michel Foucault's thought from a philosophical perspective. This goal is achieved by explaining the background and several main points of Michel Foucault's work on discourse, especially in his work including the main ideas, views and reasoning of his empiricalism through existing ideas of discourse by looking at the phenomena of oligarchy and poverty. Alleviating poverty in Malaysia is a government priority. One of the poverty alleviation policies is the implementation of e-government in alleviating poverty through the e-Kasih system. Extreme poverty in Malaysia as of March 15 2023 reached 123,243 heads of families. Efforts that have been made to resolve this problem include the People's Income Initiative (IPR) and Rahmah Cash Donations (STR) to 400 thousand people who are included in vulnerable groups. The locus of international service activities that will be carried out in the state of Malaysia is Terengganu. Terengganu, or in full Terengganu Darul Iman, is one of the states of Malaysia. It is hoped that by implementing this discourse concept, it can provide solutions or solutions to efforts to eradicate poverty in the oligarchic political system, especially in the State of Terengganu Darul Iman, Malaysia. The aim of implementing this PKM activity is to provide outreach and education regarding the concept of discourse in efforts to eradicate poverty in the State of Terengganu Darul Iman, Malaysia, in line with the National Research Master Plan 2017 - 2045 in the social sector and the Master Plan for Research and Community Service at Riau Islamic University 2021-2025 in the social sector with the alleviation of poverty.